Franco-British relations and the question of conscription in Britain, 1938-1939 - Hucker, Daniel (Cambridge University Press, 2008)
This article examines the relationship interaction between the French campaign for the introduction of British conscription during 1938-39 and the ebbs and flows of British public opinion on the same issue. In particular, it will demonstrate how French pressure for conscription varied in intensity depending on their perceptions of British opinion on the subject. It was this interaction between diplomatic and domestic pressures that ultimately compelled the British government to introduce conscription in April 1939. Furthermore, the issue of conscription also sheds light on the wider issue of Franco-British relations, revealing how French foreign policy was neither dictated by an ‘English Governess’ nor pursued independently of Great Britain.